Reduction of the amyloidogenicity of a protein by specific binding of ligands to the native conformation - Chiti, Fabrizio (Cold Spring Harbor Laboratory Press, 2001)
It is known that human muscle acylphosphatase (AcP) is able, under appropriate conditions in vitro, to aggregate and form amyloid fibrils of the type associated with human diseases. A number of compounds were tested for their ability to bind specifically to the native conformation of AcP under conditions favoring denaturation and subsequent aggregation and fibril formation. Compounds displaying different binding affinities for AcP were selected and their ability to inhibit protein fibrillization in vitro was evaluated. We found that compounds displaying a relatively high affinity for AcP are able to significantly delay protein fibrillization, mimicking the effect of stabilizing mutations; in addition, the effectiveness of such outcome correlates positively to both ligand concentration and affinity to the native state of AcP. By contrast, the inhibitory effect of ligands on AcP aggregation disappears in a mutant protein in which such binding affinity is lost. These results indicate that the stabilization of the native conformation of amyloidogenic proteins by specific ligand binding can be a strategy of general interest to inhibit amyloid formation in vivo.